1982
DOI: 10.1128/aac.22.5.743
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between aminoglycosides and cephalosporins with antipseudomonal activity: interaction index and killing curve method

Abstract: Combinations of gentamicin with cefotaxime, moxalactam, and ceftazidime were tested against 43 bacterial strains, most of them blood isolates. With an interaction index of 0.5 as borderline, synergism was demonstrated against 30 to 40% of the strains by the fractional inhibitory concentration index and against 50 to 70% by the fractional bactericidal concentration index. The reproducibility of the index was within ±0.2 for two-thirds of 40 repetitive assays and within ±0.4 to 0.5 for all of these assays. Simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
1
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(100 citation statements)
references
References 25 publications
2
95
1
2
Order By: Relevance
“…The FIC index is the sum of the FIC for each drug in combination, and the FBC index is the sum of the FBC of each drug in combination (3). Synergism was defined as an FIC or FBC index of c0.5 for combinations involving two drugs (3,11), and an FIC or FBC index of 0.75 for combinations of three drugs (11), based on the definition of Berenbaum (1). FIC and FBC indices of sparfloxacin in combination with ethambutol or rifampin or both are shown in Table 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The FIC index is the sum of the FIC for each drug in combination, and the FBC index is the sum of the FBC of each drug in combination (3). Synergism was defined as an FIC or FBC index of c0.5 for combinations involving two drugs (3,11), and an FIC or FBC index of 0.75 for combinations of three drugs (11), based on the definition of Berenbaum (1). FIC and FBC indices of sparfloxacin in combination with ethambutol or rifampin or both are shown in Table 2.…”
mentioning
confidence: 99%
“…The FIC was calculated as the MIC of drug in combination divided by the MIC of drug alone, and the FBC was calculated as the MBC(AFB) of drug in combination divided by the MBC(AFB) of drug alone (3). The FIC index is the sum of the FIC for each drug in combination, and the FBC index is the sum of the FBC of each drug in combination (3).…”
mentioning
confidence: 99%
“…A recent study indicated that the ethanolic extract of G. kola seed did not affect the activity of some fluoroquinolone antibioticsnorfloxacin and pefloxacin -in vitro 12 . It was demonstrated, however, in a recent in vivo study that the interaction between an aqueous seed extract of G. kola and ciprofloxacin hydrochloride against Staphylococcus aureus showed a biphasic effect of an antagonistic effect at an earlier stage and a potentiative (additive) effect at a later stage 10 .…”
Section: Discussionmentioning
confidence: 99%
“…A probable explanation of this enhanced activity in combination is that the gatifloxacin and the antimicrobial principles in methanol extract of G. kola seed may possibly have different mechanisms of action or may be inhibiting two different steps in the same biosynthetic pathway of the organism resulting in an overall synergy at certain combinations. Gatifloxacin is known to act by preventing bacterial replication through inhibition of DNA gyrase while the mechanism of action of G. kola seed extract is yet to be completely elucidated 10 . However, it has been noted that two antimicrobial agents may interact antagonistically if one is bacteriostatic and the other is bactericidal 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the introduction of new compounds into clinical use has helped to curtail the spread of resistant pathogens, resistance to such new drugs, has developed in some cases. It has been observed by several studies that antibiotic combinations can have synergistic benefits and interactions between existing antibiotics (Bayer et al, 1980;Hallander et al, 1982;Hooton et al, 1984;Cottagnoud et al, 2000; instaed of Bayer et al, 1980;Hooton et al, 1984;Cottagnoud et al, 2000;Hallander et al, 1982.). Several current therapeutic regimes are based on synergistic interactions between antibiotics with different target sites.…”
Section: The Use Of Resistance Modifying Agents In Combination With Amentioning
confidence: 99%